(3gOGjI GdMGFQ aj eYGfi JMaI GdCUGZQs - (3CMeO Hf eMeO GdMGLj GdYHOdj GdfLjHjs ((3eMeO Hf eMfV Hf CMeO Hf Hhce s)
(3ChdgG (B:s
(3hHYO ajbhd gPG JYdjb dWja Ydi fXefG GdeSei HJMaI GdCUGZQ Cjef ajg ZGdHkG ehVY GdcdeGJ ef GdShQI GdJi JYRI EdjgG GdMeO , Ci GdcdGe KGHJ heSJMb s
(3BNQgG (B:s
(3hde jcf ajgf HGdeSJhLH , EP bO jJNda , hdfbJUQ Ydi GdPi ChajfG Nha GdSBeI ef Gdedd , EPG SJhajfG LejY GdfXGFQ hGdVhGHW , hGddg fMeO GfJgi s
(3HYV YHGQGJgG HGdMeQIs
(3fSNI LjOIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs